DEGUM recommendations on infection prevention in ultrasound and endoscopic ultrasound = DEGUM-Empfehlungen zur Hygiene in Sonografie und Endosonografie - Müller, Thomas; Heil, Jörg (Ultraschall in der Medizin, 2018)
Microbial contamination of ultrasound probes for percutaneous or endoscopic use is common. However, infectious diseases caused by transmission of microorganisms by US procedures have rarely been reported. In Germany, legal regulations address hygiene in ultrasound procedures. Based on these regulations and the available literature, an expert panel of the German Society of Ultrasound in Medicine (DEGUM) has formulated sophisticated recommendations on hygienic measures in percutaneous and endoscopic US, including US-guided interventions.
Gesehen am 20.05.2019